Analisa variasi arus listrik pada proses pengelasan Shielded Metal Arc Welding (SMAW) baja karbon sedang terhadap kekuatan bending hasil pengelasan - Heru Setiawan; Tri Cahyo Wahyudi; Muh Thohirin (Universitas Muhammadiyah Metro, 2022)
Welding is a process of joining two or more metals into a form of connection using a heat process. This study aims to determine the value of the bending test strength on SMAW welding using the E6013 electrode, using variations of electric current, namely 100A, 110A, 120A and cooling media. The welding method used is SMAW welding with AISI 1037/ST37 material. The type of seam used is V-slope with a slope of 600 according to AWS d1.1:2000 standardization. The test carried out is a bending test using the Three Point Bending method. The value of the bending stress at room temperature media is 113.3 kgf at a current of 110A with the lowest value. For the current strength of 120A, the largest is 117.3 kgf. The value of the bending stress on mineral water immersion media is 103 kgf at a current of 120A with the lowest value. For a current of 100A, the largest is 110.3 kgf.